Statiny a chirurgická revaskularizace - jaký je prospěch? - Koenig, M. A (Clinical Cardiology Alert, 2010)
Statin use before surgery has been associated with reduced morbidity and mortality after vascular surgery. The effect of preoperative statin use on stroke and encephalopathy after coronary artery bypass grafting (CABG) is unclear. METHODS: A post hoc analysis was undertaken of a prospectively collected cohort of isolated CABG patients over a 10-year period at a single institution. Primary outcomes were stroke and encephalopathy. Univariable analyses identified risk factors for statin use, which were applied to a propensity score model using logistic regression and patients were divided into quintiles of propensity for statin use. Controlling for propensity score quintile, the odds ratio (OR) of combined stroke and encephalopathy (primary endpoint), cardiovascular mortality, myocardial infarction, and length of stay were compared between statin users and nonusers. RESULTS: There were 5,121 CABG patients, of whom 2,788 (54%) were taking statin medications preoperatively. Stroke occurred in 166 (3.2%) and encephalopathy in 438 (8.6%), contributing to 604 patients (11.8%) who met the primary endpoint. The unadjusted OR of stroke/encephalopathy in statin users was 1.053 (95% confidence interval [CI] 0.888-1.248, p = 0.582). Adjustment based on propensity score resulted in balance of stroke risk factors among quintiles. The propensity score-adjusted OR of stroke/encephalopathy in statin users was 0.958 (95% CI 0.784-1.170, p = 0.674). There were no significant differences in cardiovascular mortality, myocardial infarction, or length of stay between statin users and otherwise similar nonusers. CONCLUSIONS: In this large data cohort study, preoperative statin use was not associated with a decreased incidence of stroke and encephalopathy after coronary artery bypass grafting.
Keywords: financování organizované; Female; ženské pohlaví; cévní mozková příhoda; Enzyme Inhibitors; lidé; Stroke; databáze faktografické; Treatment Failure; statiny; kohortové studie; Financing, Organized; Brain Diseases; Incidence; Cohort Studies; Middle Aged; prospektivní studie; Male; Hydroxymethylglutaryl-CoA Reductase Inhibitors; incidence; Aged; Prospective Studies; nemoci mozku; inhibitory enzymů; neúspěšná terapie; předoperační péče; koronární bypass; Preoperative Care; Databases, Factual; lidé středního věku; senioři; mužské pohlaví; Coronary Artery Bypass; Propensity Score; Humans